Environmental filters and biotic interactions drive species richness and composition in ecotone forests of the northern Brazilian Amazonia - Silva, Williamar Rodrigues; Pequeno, Pedro Aurélio Costa Lima; Farias, Hugo Leonardo Sousa; Melo, Valdinar Ferreira; Villacorta, Carlos Darwin Angulo; Carvalho, Lidiany Camila Silva; Perdiz, Ricardo Oliveira; Citó, Arthur Camurça; Barbosa, Reinaldo Imbrozio (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2021)
The structure of tree communities in tropical forests depends on environmental filters and biotic interactions such as competition and facilitation. Many ecotone forests in Northern Amazonia are intriguingly populated by tree assemblages characterized by distinct abundances of a single species, Peltogyne gracilipes (Leguminosae). It is unclear whether this pattern solely reflects environmental filters or also antagonistic interactions among species with similar habitat requirements. The aim of this study was to determine the response of species richness and composition to environmental filters, and analyze the role of P. gracilipes in structuring tree communities in ecotone forest areas of the Northern Brazilian Amazonia. We sampled 129 permanent plots along a hydro-edaphic gradient. All arboreal individuals with stem diameter ≥10 cm were measured and identified. Multiple regressions were performed to test the effects of environmental filters, and abundance of P. gracilipes on the tree species richness and composition. Species richness and composition responded to the same filters which, in turn, affected species composition directly and indirectly, through the abundance of P. gracilipes. Our results indicate that both abiotic filters and biotic interactions shape the studied tree communities. P. gracilipes can be considered an indicator species of hydro-edaphic conditions, but also is itself a driver of tree community structure.